Laboratory studies of the role of bandwidth in surface transport and energy dissipation of deep-water breaking waves. (25th November 2021) - Sinnis, James T.; Grare, Laurent; Lenain, Luc; Pizzo, Nick
Abstract: Abstract : This paper presents laboratory measurements of surface transport due to non-breaking and breaking deep-water focusing surface wave packets and examines the dependence of the transport on the wave packet bandwidth, . This extends the work of Deike et al. ( J. Fluid Mech., vol. 829, 2017, pp. 364–391) and Lenain et al. ( J. Fluid Mech., vol. 876, 2019, p. R1), where similar numerical and laboratory experiments were conducted, but the bandwidth was held constant. In this paper, it is shown that the transport is strongly affected by the bandwidth. A model for the horizontal length scale of the breaking region is proposed that incorporates the bandwidth, central frequency, the linear prediction of the slope at focusing and the breaking threshold slope of the wave packet. This is then evaluated with data from archived and new laboratory experiments, and agreement is found. Furthermore, the horizontal length scale of the breaking region implies modifications to the model of the energy dissipation rate from Drazen et al. ( J. Fluid Mech., vol. 611, 2008, pp. 307–332). This modification accounts for differing trends in the dissipation rate caused by the bandwidth in the available laboratory data.